Determining the ensiling characteristics of potato vine silage supplemented with rice bran and corn and evaluating their ruminal fermentation potential in vitro. Issue 2 (2nd April 2020) - Guo, Yanli; Han, Haizhu; Luo, Ruirui; Zhao, Fangfang
ABSTRACT: The effects of rice bran and corn on ensiling characteristics of potato vines were investigated. Ruminal fermentation of potato vine silage was measured using a rumen simulation technique (Rusitec). Potato vines were treated (fresh weight basis) for ensiling without additives (control), with 15% rice bran and with 15% rice bran plus 3% corn, 5% corn, or 7% corn, respectively. Silage with 5% corn was chosen for a ruminal fermentation trial, based on the results of ensiling quality. Comparison of rumen fermentation between two silage (silage with 5% corn and whole corn silage) diets was conducted using a Rusitec apparatus. Adding rice bran and corn improved the potato vine silage quality ( P < .05). Compared with whole corn silage, potato vine silage diet had lower ( P < .05) methane production, ruminal pH, acetate, and acetate to propionate ratio and higher ( P < .05) total volatile fatty acids, total nitrogen (N), ammonia-N, and microbial-N. These findings indicated that rice bran and corn improved ensiling fermentation characteristics of potato vines, and that additive-treated potato vine silage had no adverse effects on rumen fermentation and could improve the energy and N utilisation and alleviate the methane pollution of the rumen compared with whole corn silage.